ACCOUNTING OF ELECTRONIC MONEY IN BANKS - Avlayev Nurbek Mahmasaid ogli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article discusses the accounting system for electronic money in commercial banks, its economic content, and the procedure for its reflection in financial statements. Electronic of money national payment​ in the system place and they with related operations into account in receiving to the surface coming problems analysis Also, international​​ financial report to the standards appropriate electronic the money right​ classification and assessment methods seeing Research​​ results banks in the activity digital assets into account to take efficiency to increase service does.